Mobile Summon System - Omar, Mohd Adzlan (Universiti Teknologi Petronas, 2006)
This paper is research on the mobile commerce (m-commence) and WAP-enable applications that will be used in developing a Mobile Summon System. With the Mobile Summon System, it has capabilities to help users in making payment for summons. Portable mobile devices such as mobile phones were used as a medium in making the transaction. This report started with the introduction of the project which consists of the background study, problem statement and the objective for this project. The current payment for summon was making by using manually and via online services (ecommence). Thus, the objective of developing Mobile Summon System is to improving in payment system and to make users more convenience in terms of making payment. Then, there is the literature review from journals, books, magazines and internet. The literature review is the major reference in developing this project. The methodologies that have been used during developing the system are waterfall approach as well as decision support system. The waterfall approach consists of five phases which are requirement analysis, system requirements, design, coding and finally testing. Result and discussion describes on the interfacesand the outputof the system. The final part of this paper is the conclusion and recommendation.